Uptake of Schistosoma mansoni extracellular vesicles by human endothelial and monocytic cell lines and impact on vascular endothelial cell gene expression. Issue 9 (August 2020) - Kifle, Desalegn Woldeyohannes; Chaiyadet, Sujittra; Waardenberg, Ashley J.; Wise, Ingrid; Cooper, Martha; Becker, Luke; Doolan, Denise L.; Laha, Thewarach; Sotillo, Javier; Pearson, Mark S.; Loukas, Alex
Graphical abstract: Highlights: Schistosoma mansoni secreted extracellular vesicles (EVs) are internalised by human endothelial and monocyte cell lines. Internalisation of EVs induces differential gene expression in vascular endothelial cells. Differentially expressed genes are involved in intravascular parasitism pathways including coagulation and inflammation. Antibodies raised to S. mansoni EV tetraspanins block the uptake of vesicles by host endothelial and monocyte cell lines. Abstract: The ability of the parasitic blood fluke Schistosoma mansoni and other parasitic helminths to manipulate host biology is well recognised, but the mechanisms that underpin these phenomena are not well understood. An emerging paradigm is that helminths transfer their biological cargo to host cells by secretion of extracellular vesicles (EVs). Herein, we show that two populations of S. mansoni secreted EVs – exosome-like vesicles (ELVs) and microvesicles (MVs) – are actively internalised in two distinct human cell lines that reflect the resident cell types encountered by the parasite in vivo: human umbilical vein endothelial cells (HUVECs) and THP-1 monocytes. RNA-sequencing of HUVECs co-cultured with S. mansoni ELVs compared with untreated HUVECs revealed differential expression of genes associated with intravascular parasitism, including vascular endothelial contraction, coagulation, arachidonic acid metabolism and immune cell trafficking and signalling. Finally, we show that antibodies raised against recombinant tetraspanin (TSP) proteins from the surface of S. mansoni EVs significantly blocked EV uptake by both HUVECs and THP-1 monocytes whereas pre-immunisation antibodies did not. To our knowledge, this is the first evidence demonstrating the internalisation of secreted EVs from any helminth into vascular endothelial cells, providing novel insight into the potential mechanisms underlying host-schistosome interactions. The ability of anti-TSP antibodies to block vesicle uptake by host target cells further supports the potential of TSPs as promising antigens for an anti-fluke vaccine. It also suggests a potential mechanism whereby the current candidate human schistosomiasis vaccine, Sm -TSP-2, exerts its protective effect in animal models.